High-laser-transmittance PBT / PET / EP alloy and preparation method thereof
By using modified chopped glass fibers in PBT/PET/EP alloys, the light transmittance and mechanical properties of the material are improved, and the problem of insufficient performance of glass fiber reinforced PBT materials in the prior art is solved, thereby achieving high laser transmittance and performance suitable for high-end manufacturing fields.
Patent Information
- Application Number
- CN202510220598.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-27
AI Technical Summary
The prior art still has limitations in improving the light transmittance and performance of glass fiber reinforced PBT materials in complex environments, and it is difficult to meet the precision welding needs of high-end fields such as automobile manufacturing.
By selecting specific combinations of PBT, PET and EP and performing radio frequency magnetron sputtering treatment on glass fibers with alumina as the target, modified chopped glass fibers are obtained to improve the light transmittance and mechanical properties of the alloy material.
The laser transmittance of 980nm at a thickness of 2mm is achieved to reach 50%. At the same time, the alloy has good mechanical properties and heat resistance, and is suitable for the manufacture of electromechanical actuator shells such as eddy current control.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of engineering plastic alloy materials and relates to a PBT / PET / EP alloy with high laser transmittance and a preparation method thereof. Background Art
[0002] With the rapid development of the automobile manufacturing industry, lightweight design has become an important development direction of the automobile manufacturing industry. More and more plastic products are replacing metal parts in automobile manufacturing. Laser welding is a method of irradiating a laser beam on a laminated resin molded body so that it passes through the irradiated surface and is absorbed on the other side for melting and fusion. Compared with other plastic welding methods, plastic laser welding has the advantages of beautiful welds, small welding deformation, and high strength. In addition, plastic laser welding can also achieve connection from two-dimensional to three-dimensional space, breaking the constraints of structure and shape, and has the advantage of high automation, which is suitable for the precision welding needs of high-end fields such as automobile manufacturing.
[0003] Polybutylene terephthalate (PBT) is a crystalline polymer with low transmittance. The transmittance of glass fiber reinforced PBT is even lower and is mainly affected by crystallinity and grain size. At present, domestic and foreign scientific and technological workers have achieved remarkable results in the modification research of glass fiber reinforced PBT materials with high laser transmittance. For example, Kingfa Technology studied the effects of glass fiber content, glass fiber diameter and inorganic reactive nucleating agent sodium carbonate on the transmittance of glass fiber reinforced PBT; BASF successfully modified the morphology of PBT, increasing the laser transmittance from 30% to nearly 60%.
[0004] However, the existing technology still has certain limitations, and there is still room for improvement in further improving the light transmittance of glass fiber reinforced PBT and improving its performance in complex environments. In order to solve the above problems, the present invention studies the laser transmittance performance of PBT / PET / EP alloy materials, in order to meet the requirements of being applied to the manufacture of housings of electromechanical actuators for eddy current control, for example. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention selects specific PBT, PET and EP, and performs radio frequency magnetron sputtering treatment on the glass fiber using alumina as a target to obtain modified chopped glass fiber. The components interact with each other to improve the light transmittance of the alloy material.
[0006] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, a high laser transmittance PBT / PET / EP alloy is provided, wherein the alloy comprises the following raw material components in weight percentage: Polybutylene terephthalate 30%-40%; Polyethylene terephthalate 10%-30%; Epoxy resin 5%-10%; Lubricant 0.2%-0.5%; Antioxidant 0.2%-0.5%; Glass fiber 20%-40%; Black dye 0.5%-1.5%; The glass fiber is a modified short glass fiber that is treated with radio frequency magnetron sputtering using aluminum oxide as a target material; the treatment process of the modified short glass fiber is as follows: the short glass fiber is placed in a sodium hydroxide solution for cleaning, and then washed with clean water and placed in a pretreatment agent, stirred, and dried to obtain the pretreated glass fiber; the pretreated glass fiber is used as a substrate and aluminum oxide is used as a target material to perform radio frequency magnetron sputtering to obtain the modified short glass fiber; the pretreatment agent is a cyclohexylaminopropyltrimethoxysilane aqueous solution with a mass fraction of 3%-5%.
[0007] As a preferred embodiment of the present invention, the polybutylene terephthalate (PBT) has a relative viscosity of 1.0±0.015 dl / g.
[0008] As a preferred embodiment of the present invention, the polyethylene terephthalate (PET) has an intrinsic viscosity of 0.68±0.01 dl / g.
[0009] As a preferred embodiment of the present invention, the epoxy resin (EP) is a bisphenol A epoxy resin with an equivalent weight of 730-840 g / eq.
[0010] As a preferred embodiment of the present invention, the alumina is α-phase alumina with a particle size of 40-80 nm.
[0011] As a preferred embodiment of the present invention, the lubricant is a mixture of a copolymer and a bead-shaped or flake-shaped wax.
[0012] As a preferred embodiment of the present invention, the antioxidant is selected from one or a combination of antioxidant 1076, antioxidant 1010, antioxidant CA, antioxidant 2246, antioxidant 168, antioxidant 1098, and antioxidant 626.
[0013] As a preferred embodiment of the present invention, the black dye is a chemical dye, and its chemical name is 2-sodium pyridyl-1,3-phenylenedihydrazine trisulfonate.
[0014] In a second aspect, the present invention provides a method for preparing the aforementioned PBT / PET / EP alloy, the method comprising the following steps: Weigh the formulated amounts of PBT, PET, EP, lubricant, antioxidant, glass fiber and black dye, put them into a high-speed mixer, mix and process, discharge, and then extrude and granulate them using a twin-screw extruder, wherein the glass fiber is fed into the twin-screw extruder from a side feed port, and the PBT / PET / EP alloy is obtained through extrusion and granulation.
[0015] As a preferred embodiment of the present invention, the processing temperature of the twin-screw extruder is 250-270°C, the screw speed is 240-360 r / min; the length of the material strip passing through water is 5-7m, and the water temperature is controlled at -5°C~0°C.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts a specific combination of PBT, PET and EP, which interacts with glass fibers, lubricants and the like in the system, to achieve a transmittance of 50% under 980nm laser conditions at a thickness of 2 mm. The alloy also has good mechanical properties and heat resistance, and can be used to manufacture the housing of an electromechanical actuator for eddy current control, for example. DETAILED DESCRIPTION
[0017] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the present invention is further described in detail below. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0018] The specific implementation of the present invention provides a high laser transmittance PBT / PET / EP alloy, which includes the following raw material components in weight percentage: Polybutylene terephthalate 30%-40%; Polyethylene terephthalate 10%-30%; Epoxy resin 5%-10%; Lubricant 0.2%-0.5%; Antioxidant 0.2%-0.5%; Glass fiber 20%-40%; Black dye 0.5%-1.5%.
[0019] As a more preferred embodiment of the present invention, the polybutylene terephthalate, i.e. PBT, has a relative viscosity of 1.0±0.015 dl / g, and the relative viscosity is measured according to GB / T 14190-2017.
[0020] As a more preferred embodiment of the present invention, the polyethylene terephthalate, i.e. PET, has an intrinsic viscosity of 0.68±0.01 dl / g, and the intrinsic viscosity is measured by the GB / T 14190-2017 method.
[0021] As a more preferred embodiment of the present invention, the epoxy resin, namely EP, is a bisphenol A epoxy resin with an equivalent weight of 730-840 g / eq, which is measured by the GB / T 4612-2008 method.
[0022] As a preferred embodiment of the present invention, the weight percentage content of the PBT can be 30%, 32%, 34%, 36%, 38% or 40%, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable; the weight percentage content of the PET can be 10 %, 15%, 20%, 25% or 30%, etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable; the weight percentage content of the EP can be 5%, 6%, 7%, 8%, 9% or 10%, etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable; the weight percentage content of the lubricant can be 0.2%, 0.3%, 0.4% or 0.5%, etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable; the weight percentage content of the antioxidant can be 0.2%, 0.3%, 0.4% or 0.5%, etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable; the weight percentage content of the glass fiber can be 20 %, 25%, 30%, 35% or 40%, etc., but are not limited to the listed values, and other values not listed within the numerical range are equally applicable; the weight percentage content of the black dye can be 0.5%, 0.7%, 0.9%, 1.1% or 1.5%, etc., but are not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0023] As a preferred embodiment of the present invention, the glass fiber is a modified chopped glass fiber that is processed by radio frequency magnetron sputtering using aluminum oxide as a target.
[0024] As a preferred embodiment of the present invention, the alumina is α-phase alumina with a particle size of 40-80 nm.
[0025] The treatment process of the modified chopped glass fiber is as follows: the chopped glass fiber is placed in a sodium hydroxide solution for cleaning, then washed with clean water, placed in a pretreatment agent, stirred, and dried to obtain pretreated glass fiber; using the pretreated glass fiber as a substrate and aluminum oxide as a target, radio frequency magnetron sputtering treatment is performed to obtain the modified chopped glass fiber.
[0026] As a preferred embodiment of the present invention, the treatment process of the modified chopped glass fiber is as follows: the chopped glass fiber is placed in a sodium hydroxide solution with a mass fraction of 3% to 5% for washing for 20 to 30 minutes, then washed with clean water and placed in a pretreatment agent with a mass fraction of 3% to 5%, stirred, and dried to obtain pretreated glass fiber; the pretreated glass fiber is used as a substrate and alumina is used as a target material to perform radio frequency magnetron sputtering treatment to obtain modified chopped glass fiber. When alumina is used as a target material in radio frequency magnetron sputtering, the sputtering pressure is controlled to be 1.3-1.5Pa, the sputtering power is 250-280W, the sputtering time is 1.7-2h, the vacuum degree is 4.5×10-3Pa, and the argon flow rate is 30-40ml / min. The treated sample is annealed at 750-800℃.
[0027] As a preferred embodiment of the present invention, the pretreatment agent is a cyclohexylaminopropyltrimethoxysilane aqueous solution with a mass fraction of 3%-5%.
[0028] As a preferred embodiment of the present invention, the lubricant is a mixture of a copolymer and a bead-shaped or flake-shaped wax.
[0029] As a preferred embodiment of the present invention, the antioxidant is selected from one or a combination of antioxidant 1076, antioxidant 1010, antioxidant CA, antioxidant 2246, antioxidant 168, antioxidant 1098, and antioxidant 626; as a preferred embodiment of the present invention, the antioxidant includes antioxidant 168 and antioxidant 1098; as a preferred embodiment of the present invention, the mass ratio of antioxidant 168 to antioxidant 1098 is 1:(0.9-1.1); as a preferred embodiment of the present invention, the mass ratio of antioxidant 168 to antioxidant 1098 is 1:1.
[0030] As a preferred embodiment of the present invention, the black dye is a chemical dye, and its chemical name is 2-sodium pyridyl-1,3-phenylenedihydrazine trisulfonate.
[0031] The specific embodiments of the present invention also provide a method for preparing the aforementioned PBT / PET / EP alloy, the method comprising the following steps: Weigh the formulated amounts of PBT, PET, EP, lubricant, antioxidant, glass fiber and black dye, put them into a high-speed mixer, mix and process, discharge, and then extrude and granulate them using a twin-screw extruder, wherein the glass fiber is fed into the twin-screw extruder from a side feed port, and the PBT / PET / EP alloy is obtained through extrusion and granulation.
[0032] As a preferred embodiment of the present invention, the mixing processing time is 3 min-5 min, such as 3 min, 4 min or 5 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] As a preferred embodiment of the present invention, the processing temperature of the twin-screw extruder is 250°C-270°C, for example, 250°C, 255°C, 260°C, 265°C or 270°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable; the screw speed of the twin-screw extruder is 240rpm-360rpm, for example, 240 rpm, 260 rpm, 280rpm, 300rpm, 320 rpm, 340rpm or 360rpm. rpm, etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable; the water passage length of the material strip is 5-7m, for example, 5m, 5.5m, 6m, 6.5m or 7m, etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable; the water temperature is controlled at -5℃~0℃, for example, -5℃, -4℃, -3℃, -2℃, -1℃ or 0℃, etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] The following are typical but non-limiting embodiments of the present invention: The following examples include PBT (brand 1100-211S, Changchun Man-Made Resin Factory Co., Ltd.); PET (brand KH2678C, Hengli Group-Yingkou Kanghui Petrochemical Co., Ltd.); EP (brand KD-213, Guodu Chemical (Kunshan) Co., Ltd.); lubricant (brand P130, Brüggemann); antioxidants including antioxidant 168 and antioxidant 1098 (BASF, Germany), the mass ratio of antioxidant 168 to antioxidant 1098 being 1:1; glass fiber (chopped glass fiber, Taishan Glass Fiber Co., Ltd.); black dye (brand solvent black X70, Shanghai Rude Dye Chemical Co., Ltd.).
[0035] Example 1
[0036] The present embodiment provides a high laser transmittance PBT / PET / EP alloy and a preparation method thereof, wherein the alloy includes the following components in weight percentage: PBT: 35%, PET: 24%, EP: 9%, lubricant: 0.3%, antioxidant: 0.4%, glass fiber: 30%, and black dye: 1.3%.
[0037] The glass fiber is a modified short glass fiber treated by radio frequency magnetron sputtering with aluminum oxide as the target material. The treatment process of the modified short glass fiber is as follows: the short glass fiber is placed in a sodium hydroxide solution with a mass fraction of 3% to 5% for washing for 25 minutes, then washed with clean water and placed in a pretreatment agent with a mass fraction of 4%, stirred, and dried to obtain pretreated glass fiber; the pretreated glass fiber is used as the substrate and aluminum oxide is used as the target material to perform radio frequency magnetron sputtering to obtain the modified short glass fiber. When aluminum oxide is used as the target material in the radio frequency magnetron sputtering, the sputtering pressure is controlled to be 1.4 Pa, the sputtering power is 270 W, the sputtering time is 1.8 h, and the vacuum degree is 4.5×10 -3 Pa, argon flow rate is 35ml / min, and the treated sample is annealed at 780°C; the alumina is α-phase alumina, purchased from TAP-A26 of Fangyu Chemical; the pretreatment agent is a cyclohexylaminopropyltrimethoxysilane aqueous solution with a mass fraction of 3%-5%.
[0038] The preparation method of the PBT / PET / EP alloy comprises: Weigh the formulated amounts of PBT, PET, EP, lubricant, antioxidant, glass fiber and black dye and put them into a high-speed mixer for mixing and processing. Then, the material is extruded and granulated using a twin-screw extruder, wherein the glass fiber is fed into the twin-screw extruder from the side feed port, and the PBT / PET / EP alloy is obtained by extrusion granulation. The mixing processing time is 4 minutes, the processing temperature of the twin-screw extruder is 260°C, and the screw speed is 300 r / min; the water-passing length of the material strip is 6 m, and the water temperature is controlled at -3°C.
[0039] Example 2
[0040] The present embodiment provides a high laser transmittance PBT / PET / EP alloy and a preparation method thereof, wherein the alloy includes the following components in weight percentage: PBT: 33%, PET: 20%, EP: 6%, lubricant: 0.2%, antioxidant: 0.2%, glass fiber: 40%, and black dye: 0.6%.
[0041] The processing process of the glass fiber is the same as that in Example 1.
[0042] The preparation method of the PBT / PET / EP alloy is the same as that in Example 1.
[0043] Example 3
[0044] The present embodiment provides a high laser transmittance PBT / PET / EP alloy and a preparation method thereof, wherein the alloy includes the following components in weight percentage: PBT: 40%, PET: 23%, EP: 10%, lubricant: 0.3%, antioxidant: 0.3%, glass fiber: 25%, and black dye: 1.4%.
[0045] The processing process of the glass fiber is the same as that in Example 1.
[0046] The preparation method of the PBT / PET / EP alloy is the same as that in Example 1.
[0047] Comparative Example 1:
[0048] This comparative example provides a high laser transmittance PBT / PET / EP alloy and a preparation method thereof, wherein the alloy comprises the following components in weight percentage: PBT: 39%, PET: 29%, lubricant: 0.3%, antioxidant: 0.4%, glass fiber: 30%, and black dye: 1.3%.
[0049] The processing process of the glass fiber is the same as that in Example 1.
[0050] The preparation method of the PBT / PET / EP alloy is the same as that in Example 1.
[0051] Comparative Example 2:
[0052] This comparative example provides a high laser transmittance PBT / PET / EP alloy and a preparation method thereof, wherein the alloy comprises the following components in weight percentage: PBT: 35%, PET: 24%, EP: 9%, lubricant: 0.3%, antioxidant: 0.4%, glass fiber: 30%, black dye: 1.3%. The EP equivalent is 500-550 g / eq, and is purchased from KD-211G of Guodu Chemical (Kunshan) Co., Ltd.
[0053] The processing process of the glass fiber is the same as that in Example 1.
[0054] The preparation method of the PBT / PET / EP alloy is the same as that in Example 1.
[0055] Comparative Example 3:
[0056] This comparative example provides a high laser transmittance PBT / PET / EP alloy and a preparation method thereof, wherein the alloy comprises the following components in weight percentage: PBT: 35%, PET: 24%, EP: 9%, lubricant: 0.3%, antioxidant: 0.4%, glass fiber: 30%, black dye: 1.3%. The EP equivalent is 875-975 g / eq, and is purchased from KD-214C of Guodu Chemical (Kunshan) Co., Ltd.
[0057] The processing process of the glass fiber is the same as that in Example 1.
[0058] The preparation method of the PBT / PET / EP alloy is the same as that in Example 1.
[0059] Comparative Example 4:
[0060] This comparative example provides a high laser transmittance PBT / PET / EP alloy and a preparation method thereof, wherein the alloy comprises the following components in weight percentage: PBT: 35%, PET: 24%, EP: 9%, lubricant: 0.3%, antioxidant: 0.4%, glass fiber: 30%, and black dye: 1.3%.
[0061] The treatment process of the glass fiber is the same as that in Example 1, except that the alumina is α-phase alumina with a particle size of 300 nm, which is TAP-A30G from Fangyu Chemical.
[0062] The preparation method of the PBT / PET / EP alloy is the same as that in Example 1.
[0063] Comparative Example 5:
[0064] This comparative example provides a high laser transmittance PBT / PET / EP alloy and a preparation method thereof, wherein the alloy comprises the following components in weight percentage: PBT: 35%, PET: 24%, EP: 9%, lubricant: 0.3%, antioxidant: 0.4%, glass fiber: 30%, and black dye: 1.3%.
[0065] The processing process of the glass fiber is the same as that in Example 1, except that the alumina is α-phase alumina with a particle size of 30 nm, which is VK-L30 from Xuancheng Jingrui New Materials.
[0066] The preparation method of the PBT / PET / EP alloy is the same as that in Example 1.
[0067] Comparative Example 6:
[0068] This comparative example provides a high laser transmittance PBT / PET / EP alloy and a preparation method thereof, wherein the alloy comprises the following components in weight percentage: PBT: 35%, PET: 24%, EP: 9%, lubricant: 0.3%, antioxidant: 0.4%, glass fiber: 30%, and black dye: 1.3%.
[0069] The processing process of the glass fiber is the same as that in Example 1, except that the alumina is γ-phase alumina with a particle size of 30-50 nm, SS-LY30 from Jikang New Materials.
[0070] The preparation method of the PBT / PET / EP alloy is the same as that in Example 1.
[0071] Comparative Example 7:
[0072] This comparative example provides a high laser transmittance PBT / PET / EP alloy and a preparation method thereof, wherein the alloy comprises the following components in weight percentage: PBT: 35%, PET: 24%, EP: 9%, lubricant: 0.3%, antioxidant: 0.4%, glass fiber: 30%, and black dye: 1.3%.
[0073] The treatment process of the glass fiber is the same as that in Example 1, except that the pretreatment agent is KH550.
[0074] The preparation method of the PBT / PET / EP alloy is the same as that in Example 1.
[0075] Comparative Example 8:
[0076] This comparative example provides a high laser transmittance PBT / PET / EP alloy and a preparation method thereof, wherein the alloy comprises the following components in weight percentage: PBT: 35%, PET: 24%, EP: 9%, lubricant: 0.3%, antioxidant: 0.4%, glass fiber: 30%, and black dye: 1.3%.
[0077] The treatment process of the glass fiber is the same as that in Example 1, except that the modified chopped glass fiber is not pretreated.
[0078] The preparation method of the PBT / PET / EP alloy is the same as that in Example 1.
[0079] Comparative Example 9:
[0080] This comparative example provides a high laser transmittance PBT / PET / EP alloy and a preparation method thereof, wherein the alloy comprises the following components in weight percentage: PBT: 35%, PET: 24%, EP: 9%, lubricant: 0.3%, antioxidant: 0.4%, glass fiber: 30%, and black dye: 1.3%.
[0081] The treatment process of the glass fiber is the same as that in Example 1, except that the modified chopped glass fiber is only pretreated and is not subjected to RF magnetron sputtering treatment.
[0082] The preparation method of the PBT / PET / EP alloy is the same as that in Example 1.
[0083] Comparative Example 10:
[0084] This comparative example provides a high laser transmittance PBT / PET / EP alloy and a preparation method thereof, wherein the alloy comprises the following components in weight percentage: PBT: 35%, PET: 24%, EP: 9%, lubricant: 0.3%, antioxidant: 0.4%, glass fiber: 30%, and black dye: 1.3%.
[0085] The treatment process of the glass fiber is the same as that in Example 1, except that the glass fiber is not subjected to modification treatment, that is, no pretreatment or radio frequency magnetron sputtering treatment is performed.
[0086] The preparation method of the PBT / PET / EP alloy is the same as that in Example 1.
[0087] The alloys prepared in Examples 1-3 and Comparative Examples 1-10 were subjected to performance testing using the ISO standard, where LPKF represents the transmittance of a 980nm infrared laser through a 2.0mm thick plate. The test results are shown in Tables 1 and 2 below.
[0088] Table 1: Alloy performance test results of Examples 1-3
[0089] Table 2: Alloy performance test results of comparative examples 1-10
[0090] From the comparison in the above table, it can be seen that in Example 1 and Comparative Examples 1-3, when the EP addition amount is 0% or the equivalent content of EP is changed, the mechanical properties, temperature resistance and light transmittance of the alloy will be affected, especially the light transmittance. This may be because EP and its equivalent content affect the degree of chemical reaction and interface bonding between PBT, PET and glass fiber, and the molecular network structure formed by it may lead to uneven distribution of local refractive index. However, the present invention unexpectedly found that in the system of the present invention, only when the EP equivalent content is controlled at 730-840g / eq, a better interface bonding state can be constructed between PBT, PET and glass fiber and other components, significantly improving the comprehensive performance of the alloy.
[0091] Compared with Example 1, the α-phase alumina particle size selected in Comparative Example 4 is 300nm, the α-phase alumina particle size selected in Comparative Example 5 is 30nm, and the alumina selected in Comparative Example 6 is γ-phase alumina with a particle size of 30-50nm, and the light transmittance of the alloy is deteriorated. In particular, when the α-phase alumina is 30nm, it will also affect the mechanics and temperature resistance of the alloy material. This may be because the smaller the particle size, the more likely it is to agglomerate, which increases light scattering and absorption on the one hand, and is difficult to disperse evenly on the other hand, which is prone to produce stress concentration points. Among them, when the alumina is γ-phase alumina, the temperature resistance is significantly affected, which may be because the decrease in crystal stability easily reduces the temperature resistance of the alloy material. In Comparative Example 9, the glass fiber is not sputtered, which has a great influence on the light transmittance, heat resistance and mechanical properties of the alloy material, further illustrating that the present invention adopts α-phase alumina with a particle size of 40-80 nm as the target material, and sputters the glass fiber. At this time, not only can the interface bonding between the glass fiber and the PBT / PET / EP matrix be significantly improved, and the transmittance of the 980nm infrared laser through the 2.0mm thick plate be increased, but also the mechanical properties and heat resistance of the material are better.
[0092] In Comparative Example 7, the pretreatment agent of the glass fiber is replaced by KH550 from cyclohexylaminopropyltrimethoxysilane, the glass fiber is not pretreated in Comparative Example 8, and the glass fiber is not modified in Comparative Example 10, the light transmittance is reduced, and the mechanical properties and heat resistance of the alloy material are significantly affected. This may be because in the system of the present invention, cyclohexylaminopropyltrimethoxysilane has special steric hindrance and intermolecular force, can be tightly combined with the glass fiber and the alloy matrix, optimize the interface structure, strengthen stress transfer, and improve the mechanical properties of the alloy. Its stable interface also helps to maintain the stability of the material structure and enhance heat resistance at high temperatures; and pretreating the glass fiber with cyclohexylaminopropyltrimethoxysilane can form a transition layer between the glass fiber and the sputtered film layer, which is conducive to the interfacial reaction between the glass fiber and the sputtered material during the sputtering process to form a chemical bond or alloy phase in the subsequent sputtering, thereby further enhancing the bonding force between the glass fiber and the sputtered film layer and improving the overall performance of the alloy material.
[0093] In summary, the present invention achieves a transmittance of 50% under 980nm laser conditions at a thickness of 2 mm by adopting a specific combination of PBT, PET and EP, which interacts with the glass fiber, lubricant, etc. in the system. At the same time, the alloy also has good mechanical properties and heat resistance, and can be used to manufacture the housing of an electromechanical actuator for eddy current control, for example.
[0094] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A PBT / PET / EP alloy with high laser transmittance, characterized in that: The alloy comprises the following raw material components in weight percentage: Polybutylene terephthalate 30%-40%; Polyethylene terephthalate 10%-30%; Epoxy resin 5%-10%; Lubricant 0.2%-0.5%; Antioxidant 0.2%-0.5%; Glass fiber 20%-40%; Black dye 0.5%-1.5%; The glass fiber is a modified short glass fiber that is treated with radio frequency magnetron sputtering using aluminum oxide as a target material; the treatment process of the modified short glass fiber is as follows: the short glass fiber is placed in a sodium hydroxide solution for cleaning, and then washed with clean water and placed in a pretreatment agent, stirred, and dried to obtain the pretreated glass fiber; the pretreated glass fiber is used as a substrate and aluminum oxide is used as a target material to perform radio frequency magnetron sputtering to obtain the modified short glass fiber; the pretreatment agent is a cyclohexylaminopropyltrimethoxysilane aqueous solution with a mass fraction of 3%-5%.
2. The PBT / PET / EP alloy according to claim 1, characterized in that: The polybutylene terephthalate (PBT) has a relative viscosity of 1.0±0.015 dl / g.
3. The PBT / PET / EP alloy according to claim 1, characterized in that: The polyethylene terephthalate, i.e. PET, has an intrinsic viscosity of 0.68±0.01 dl / g.
4. The PBT / PET / EP alloy according to claim 1, characterized in that: The epoxy resin, EP, is a bisphenol A epoxy resin with an equivalent weight of 730-840 g / eq.
5. The PBT / PET / EP alloy according to claim 1, characterized in that: The alumina is α-phase alumina with a particle size of 40-80 nm.
6. The PBT / PET / EP alloy according to claim 1, characterized in that: The lubricant is a mixture of a copolymer and wax in the form of beads or flakes.
7. The PBT / PET / EP alloy according to claim 1, characterized in that: The antioxidant is selected from one or a combination of antioxidant 1076, antioxidant 1010, antioxidant CA, antioxidant 2246, antioxidant 168, antioxidant 1098, and antioxidant 626.
8. The PBT / PET / EP alloy according to claim 1, characterized in that: The black dye is a chemical dye, and its chemical name is 2-sodium pyridyl-1,3-phenylenedihydrazine trisulfonate.
9. A method for preparing the PBT / PET / EP alloy according to any one of claims 1 to 8, characterized in that: The preparation method comprises: Weigh the formulated amounts of PBT, PET, EP, lubricant, antioxidant, glass fiber and black dye, put them into a high-speed mixer, mix and process, discharge, and then extrude and granulate them using a twin-screw extruder, wherein the glass fiber is fed into the twin-screw extruder from a side feed port, and the PBT / PET / EP alloy is obtained through extrusion and granulation.
10. The preparation method according to claim 9, characterized in that: The processing temperature of the twin-screw extruder is 250-270°C, the screw speed is 240-360 r / min; the length of the material strip passing through water is 5-7m, and the water temperature is controlled at -5°C~0°C.
Citation Information
Patent Citations
PBT / PET alloy material and preparation method thereof
CN109486136A
Acid and alkali resistant glass fiber composite material and preparation method thereof
CN113683866A
PBT / PET alloy and preparation method and application thereof
CN114561089A
PBT / PET alloy composition with high RTI value as well as preparation method and application of PBT / PET alloy composition
CN115785625A
Treatment of inorganic material
GB8729955D0